ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) DENGAN TANAMAN BUDIDAYA DI AREAL BEKAS TAMBANG EMAS - Bernada, .; Muin, Abdurrani; Ekyastuti, Wiwik (JURNAL HUTAN LESTARI, 2016)
After gold mining, community usedtailing for cultivation. The purpose of this study were to determined the association of arbuscular mycorrhizal fungi (AMF), the genus of AMF and the roots infection of AMF of plants cultivated on tailing. This study used survey methods with purposive sampling. Soil samples were collected five points in a depth of 10cm on the rhizosphere eight species of plants. The results shows that the average of spores density is variate. The highest of spore density is Musa paradisiaca with an average of 1,057 spores, follow by Hevea Brazilliensis with an average of 841 spores, Ipomoea batatas with an average of 586 spores, Saccharum officinarum with an average of 431 spores, Solanum mologena with an average 345 spores, Capsicum frutescens with an average of 214 spores and Anthocephalus cadamba with an average of 107 spores. While the lowest is Carica papaya with an average of 56 spores. There are 2 genus of AMF spores per 100 grams of soil, they are genus Glomus with an average of 426 spores and Gigaspora with an average of 7 spores. AMF infection in the plant roots is a medium level to high level. Three species are in a medium level of AMF infection (36,67%) there are HeveaBrazilliensis, Ipomoea batatasand Carica papaya. While five species are in a high level there are Musa paradisiaca with an average of 73.33%,Solanum mologena with an average of 70%, Anthocephalus cadambawith an average of 60%, then Capsicum frutescens and Saccharum officinarum with an average of 53.33%. Key word: Arbuscular mycorrhizal fungi, gold mining.